Elemental composition of willow short rotation crops biomass depending on variety and harvest cycle. (October 2017) - Stolarski, Mariusz J.; Niksa, Dariusz; Krzyżaniak, Michał
Abstract: The use of woody biomass in thermochemical conversion is still the most popular method of obtaining bioenergy from this material. Elemental composition has a significant effect on biomass quality and parameters of the combustion process. The aim of this study was to determine the content of selected macroelements (phosphorus, potassium, magnesium, calcium, sodium and sulphur), microelements (boron, copper, iron, manganese and zinc) and trace elements (cadmium, chromium, nickel and lead) in willow biomass of two different varieties and three clones, harvested in annual, biennial and triennial cycles in north-eastern Poland. The study found significant variability between varieties/clones and harvest cycles. Biomass of the UWM 200 clone of Salix alba in triennial harvest rotation had the best parameters as a potential fuel source; it was found to contain the significantly smallest concentrations of P, K, Na, S (1.48, 5.45, 0.08, 0.35 g kg −1 DM, respectively) and Fe, Cr, Pb (208.85, 4.91, 0.83 mg kg −1, respectively). The content of all of the elements under study decreased significantly with an extended harvest cycle, and the differences, when comparing the triennial to the annual cycle, ranged from −9% to −29% for macroelements, from −7% to −48% for microelements and from −11% to −20% for trace elements. Highlights: The study showed a significant effect of the factors on the elemental composition. Extending the harvest cycle resulted in lower element concentrations. Biomass of the UWM 200 clone had the best quality parameters. K, P, Mg, Zn and Cr had the highest number of significant correlations.